The effect of COVID-19 pandemic on acute appendicitis and negative laparotomy - Melike Ordu; Sibel Çiğdem Tuncer; Ayşe Betül Öztürk; Cengizhan Kılıçaslan (Genel Tıp Dergisi)
Background/Aims: Emergency service referrals frequently depend on non-urgent problems which are easy to solve without emergency services. Emergency services should be used effectively to raise service quality, patient and personnel satisfaction. Approximately %30 of emergency service referrals are pediatric patients. Covid-19 pandemia affecting the whole world, caused a decrease in non-covid patient emergency service referral numbers, consequently medically non-emergent patient numbers decreased too. Although the number of patients with a prediagnosis of acute appendicitis did not decrease during the pandemic, negative laparotomy rates decreased due to the effective use of emergency services.